Pulmonary capillary haemangiomatosis: a distinct entity?. (27th May 2020) - Weatherald, Jason; Dorfmüller, Peter; Perros, Frédéric; Ghigna, Maria-Rosa; Girerd, Barbara; Humbert, Marc; Montani, David
Pulmonary capillary haemangiomatosis (PCH) is a rare and incompletely understood histopathological finding characterised by abnormal capillary proliferation within the alveolar interstitium, which has long been noted to share many overlapping features with pulmonary veno-occlusive disease (PVOD). But are PCH and PVOD distinct entities that occur in isolation, or are they closely intertwined manifestations along a spectrum of the same disease? The classic clinical features of both PCH and PVOD include signs and symptoms related to pulmonary hypertension, hypoxaemia, markedly impaired diffusion capacity of the lung and abnormal chest imaging with ground glass opacities, septal lines and lymphadenopathy. In recent years, increasing evidence suggests that the clinical presentation, histopathological features, genetic substrate and pathobiological mechanisms of PCH and PVOD are overlapping and usually indistinguishable. The discovery of biallelic mutations in the eukaryotic translation initiation factor 2 α kinase 4 ( EIF2AK4 ) gene in heritable PCH and PVOD greatly advanced our understanding of the overlapping nature of these conditions. Furthermore, recognition of PCH and PVOD-like changes in other pulmonary vascular diseases and in conditions that cause chronic pulmonary venous hyper-perfusion or hypertension suggests that PCH/PVOD may develop as a reactive process to various insults or injuries to the pulmonary vasculature, rather than being primary angiogenic disorders. Pulmonary capillary haemangiomatosis (PCH) is a rare condition that is clinically inseparable from pulmonary veno-occlusive disease. PCH can develops as a consequence of genetic mutations or pulmonary venous obstruction and remodelling. http://bit.ly/35TLAY4